ANALYSIS OF THE EFFECT OF SATISFACTION, EMOTIONAL BONDING AND BRAND TRUST ON CONSUMER LOYALTY OF LIP SERUM ESENSES PRODUCTS IN BEAUTY STORE PETISAH MARKET - Sanny, Annisa; Daulay, Muhammad Toyib (Journal of Community Research and Service, 2022)
This study is to analyze the effect of satisfaction, emotional bonding and brand trust on consumer loyalty for Lip Serum Esenses  , where consumers find it difficult to get products that are often out of stock at sales outlets. Furthermore, the data obtained from the distribution of questionnaires or questionnaires from 90 respondents. The model used is Multiple Linear Regression and processed using SPSS version 22.0. The results of the analysis using the coefficient of determination show that 56.9% of customer loyalty can be obtained and explained by satisfaction, emotional attachment and brand trust. While the remaining 43.1% is explained by other variables not included in this study.